(untitled) (Fiep Bulletin - online, 2021)
Background: The pathogenesis of hypertension is related high weight through activation of the sympathetic nervous system and it´s well established in adults, but what anthropometric aspect are associate whit high blood pressure. Purpose: we analyze the association of prehypertension and hypertension based on anthropometric data in Brazilian adults. Methods: The cross-sectional study was composed 3445 adults of both sexes aged between eighteen and 60 years old. The variables anthropometric and blood pressure values were obtained according to standard methods. Blood pressure was classified (nom; prehypertension and hypertension) according to the recommendations of World Health Organization and the Brazilian Society of Hypertension. We examined potential frequency of subjects with and without hypertension for each variable and used a logistic regression with blood pressure as the dependent variable while anthropometric characteristics were used as an independent variable: body mass index, waist height ratio, waist circumference, age and sex. Hypertension was related to sex, age and body mass index. Results: The males were twice as likely to develop hypertension as females. The chance of developing hypertension increased by around 1.04 times with age. In relation to body mass index, from normal group to overweight, the chance of developing hypertension nearly doubled while, the group classified as obese, it increased three times more. Conclusion: These data can be used to control public health policy and to identify groups at risk since cardiovascular diseases are a major cause of death in Brazil